Macroeconomic policies, growth, employment, and inequality in Latin America - Mario Damill; Roberto Frenkel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper examines the macroeconomic policies and outcomes experienced by the Latin American economies during the period 1990-2010. Macroeconomic policies refer to exchange rates, monetary and aggregate fiscal policies, while macroeconomic outcomes, on the other hand, refer to the patterns of growth, inflation, employment, investment, balance of payments, and the evolution of external and public debts and international reserves. The analysis includes a discussion of the effects of macroeconomic outcomes on poverty rates. With regard to policy, the study examines the changes that took place in 1997-98, and then reviews the resulting new macroeconomic configuration that was established in 2002-03. This new configuration favoured the acceleration of output growth and employment creation, and contributed to reducing poverty rates.
Keywords: E65; I32; N16; O54; 330; Latin American economies; macroeconomic policies; economic growth; employment; poverty rates; inequality; Wirtschaftspolitik; Makroökonomischer Einfluss; Wirtschaftswachstum; Beschäftigung; Armut; Einkommensverteilung